Tribal governance and public administration - Ortiz, James (2002)
This article examines tribal governance and its relationship with the U.S. government through the lens of laws and treaties. There are more than 550 American Indian and Alaska Native tribes in the United States. Tribes are sovereigns having their own governance structures, with rich cultures that are interwined with the founding of our nation. This calls for a renewed awareness of tribes by the field of public administration, requiring careful consideration and respect of tribal cultural, historic, and social values, which are an integral part of tribal governance. - Reproduced.
Keywords: Public administration; Tribes